QIYĀS SYABAH DALAM PENETAPAN KETENTUAN PENGHITUNGAN ZAKAT PROFESI - Manzilatul Fajriyah; Uswatun Khasanah (Al-Maslahah : Jurnal Ilmu Syariah, 2022)
This article discusses the use of qiyas syabah as a method for determining the provisions for calculating professional zakat, which includes nisab and the percentage of zakat that must be spent. This article uses qualitative approach with analytical descriptive study. The results of this study indicate that qiyas syabah is a qiyas that occurs when doubts arise to equate far 'with one of the two ashl, but then ashl is chosen which has the most similarities with far'. On the other hand, the profession has the similar to agriculture in terms of necessity for capital and effort to produce assets, so that on the basis of provisions in nisab zakat for profession are equal to the ratio for zakat on agriculture, which is 653 kg of rice. On the other hand, the profession also has similarities with gold and silver because the profession produces assets in the form of money which are means of transaction and savings assets like gold and silver so on the basis of this similarity the percentage of zakat issued in professional zakat is equal to gold and silver zakat, which is equal to 2.5% of total income.